Intensity-modulated radiotherapy combined with sequential cisplatin and fluorouracil chemotherapy for locoregionally advanced nasopharyngeal carcinoma - Wu, Mingyao (Medicine (Baltimore), 2018)
To investigate the efficacy and toxicity of intensity-modulated radiotherapy (IMRT) combined with induction-adjuvant cisplatin and fluorouracil (PF) in locoregionally advanced nasopharyngeal carcinoma (NPC). A total of 91 biopsy-proven NPC patients treated with IMRT were retrospectively analyzed. All patients received induction chemotherapy (IC) consisting of cisplatin 25 mg/m2 on day 1 to 3, and 5-Fu 2500 mg/m(2) as an intravenous infusion over 120 hours every 3 weeks for 2 cycles. Adjuvant chemotherapy of the same regime was given 28 days after the end of IMRT. A total of 87 patients completed 2 cycles of IC. During adjuvant chemotherapy phase, 74.7% patients received at least 1 cycle. With a median follow-up time of 45 months (10–123 months), the 5-year local control, regional control, distant metastasis-free (DMF) and overall survival (OS) rates were 84.1%, 86.9%, 81.3%, and 74.4%, respectively. The 5-year local control rates for patients with Stage T1-2 and T3-4 was 94.6% and 76.5%, respectively (P = .045). The 5-year DMF rates for patients with N0-1 and N2-3 diseases were 90.6% and 73.3%, respectively (P = .072). During radiotherapy (RT), 24.2% patients suffered severe acute mucositis (grade 3–4). Severe late toxicities included cranial nerve palsy in 1 patient and grade 3 hearing impairment in 1 patient. IMRT combined with induction-adjuvant chemotherapy consisting of PF regimen is well tolerated and provides satisfactory local-regional control for locoregionally advanced NPC. Further treatment strategies to control distant metastasis are needed in the future.